The state of medical ethics in Mexico - Kuthy Porter, José; de la Escosura, Gabriel (Medicina e Morale, 1990)
An analysis of the state of medical ethics in Mexico allows one to understand a serious problem faced by developing countries. They are exposed to the danger of "economic utilitarianism" in medicine, and the dehumanization of medical practice. In Mexico there is no lack of laws and regulations governing the practice of medicine in its different spheres. There are certain problems, however, which call for close examination: the inadequate investment of resources for investigation, mass-sterilization without well-informed consent, as a means of birth control, the hesitancy of many doctors as to how to handle terminal patients, because of the numerous taboos concerning death, the insufficient provision of resources for organ transplants, programs for the prevention of AIDS centered exclusively on promoting the use of the condom, etc. Hence what is needed is a serious ethical and humanistic formation of doctors. There being, however, few medical faculties in the country that include medical ethics in their curriculum, it is urgent that such be created.